INTERNALIZATION OF LEGAL AWARENESS THROUGH SELF-DEVELOPMENT MOTIVATION IN REALIZING RESILIENT AND JUST INSTITUTIONS - Subakdi; Marina Ery Setiyawati (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
Self-development is a transformative process for developing potential, talents, and personality to achieve self-actualization. In the context of national life, optimal self-development must include internalizing legal awareness so that individuals can contribute ethically and professionally. This article aims to analyze how self-development motivation plays a role in increasing legal compliance and how this impacts the realization of resilient and just institutions in Indonesia, in line with point 16 of the Sustainable Development Goals (SDGs). The method used in this paper is qualitative with a library research approach. Data were collected through a review of various scientific literature, journals, and books related to the psychology of self-development, the sociology of law, and institutional governance. The results of the discussion indicate that self-development integrated with legal awareness not only increases personal productivity but also creates individuals with the integrity to step out of their comfort zones to uphold justice. The role of guidance and counseling is crucial as a catalyst in instilling legally conscious character values. A strong correlation was found between the quality of human resources motivated to develop and the creation of social peace and the strengthening of the effectiveness of public institutions in Indonesia.